2020
DOI: 10.3390/agronomy10010109
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Hay Biochar Application into Soil Increases N2O Fluxes

Abstract: Biochar has been proposed as an amendment that can improve soil conditions, increase harvest yield, and reduce N losses through NO3− leaching and N2O emissions. We conducted an experiment to test the hay biochar mitigation effect on N2O emissions depending on its production temperature. The pot experiment consisted of the soil amendment with three different production temperature biochars (300 °C, 550 °C, 850 °C) alone and in combination with three different organic fertilizers (cattle slurry, slurry digestate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…Two holes were made in each chamber, one for a gas collection pipe and the other for a temperature sensor. Gas samples were taken over a one-hour period, at regular intervals of 20 min (i.e., at 0, 20, 40, and 60 min), using 12 mL pre-evacuated (0.3 mbar) bottles [22]. The CO 2 , N 2 O, and CH 4 concentrations of samples were determined using a GC-2014 gas chromatography system (Shimadzu Corporation, Kyoto, Japan equipped with ECD, TCD, and FID sensors as described by Loftfield et al [23].…”
Section: Gas Emissions Analysismentioning
confidence: 99%
“…Two holes were made in each chamber, one for a gas collection pipe and the other for a temperature sensor. Gas samples were taken over a one-hour period, at regular intervals of 20 min (i.e., at 0, 20, 40, and 60 min), using 12 mL pre-evacuated (0.3 mbar) bottles [22]. The CO 2 , N 2 O, and CH 4 concentrations of samples were determined using a GC-2014 gas chromatography system (Shimadzu Corporation, Kyoto, Japan equipped with ECD, TCD, and FID sensors as described by Loftfield et al [23].…”
Section: Gas Emissions Analysismentioning
confidence: 99%
“…Other studies have concluded that the application of biochar increased N 2 O emissions, which might be due to the different types of biochar used in the experiment, pyrolysis temperature of biochar preparation, and the amount of biochar [51]. For example, Escuer-Gatius et al [52] found that the hay biochar pyrolyzed at 850 • C would stimulate soil N 2 O emission. Bai et al [40] showed that straw return could promote the conversion of N into N 2 O and increased N 2 O emissions, because the C in the straw stimulated the growth of microorganisms related to N 2 O production, accelerating the nitrification rate.…”
Section: Effects Of Environmental Factors On N 2 O Emissionsmentioning
confidence: 99%
“…Due to the high concentration of stabile carbon (C) compounds, the biochar decomposes very slowly in the soil that enables the long-term removal of C from the nutrient cycles, thereby being beneficial for climate change mitigation (Sohi, 2012). Also it has been found that biochar inhibits the release of greenhouse gases from the soil, but it has not been confirmed by all studies (Cayuela et al, 2014;Feng, Zhu, 2017;Buchkina et al, 2019;Escuer-Gatius et al, 2020).…”
Section: Introductionmentioning
confidence: 99%